AN APPRAISAL OF EMPLOYEES WELFARE AND SOCIAL SECURITY MEASURES IN CENTRAL PUBLIC SECTOR ENTERPRISES - Sanyal, Joyjit; Sikidar, Sujit (International Journal of Research -GRANTHAALAYAH, 2018)
Labour plays a very important role in the industrial production of the country. The human resource managers are concerned with the management of people at work. It is necessary to secure the co-operation of labour force in order to increase the production and earn higher profits. The co-operation of labour force is possible only when they are fully satisfied with their employer and the working conditions on the job. In the past, industrialists and the employers believed that their only duty towards their employees was to pay them satisfactory wages and salaries. But in due course of time, in addition to providing monetary benefits, human treatment given to employees started to play a very important role in seeking their co-operation. Labour or employee welfare activities benefit not only the workers but also the management in the form of greater industrial efficiency. The welfare activities pay a good dividend in the long run, because they contribute a lot towards the health and efficiency of the workers and towards a high morale. On the other hand, social security has come up as a dynamic concept which is considered in all advanced countries of the world as an indispensable chapter of the national programme. Social security is that security which the society furnishes through appropriate organisation against certain risks or certain contingencies to which its members are exposed. These risks are essentially contingencies against which the individual cannot afford by his small means and by his ability or foresight alone. As the name stands for general well- being of the people it is the duty of the state to promote social security which may provide the citizens with benefits designed to prevent or cure disease, to support him when he is not able to earn and to restore him to gainful activity. The state as an employer has provided for certain measures for the welfare and social security of the labourers, who contribute towards the economic development of a country and in this regard, the government has to see towards the proper implementation of such measures to maintain a harmonious industrial relation on the one side and on the other hand towards the upliftment of the members of the society. Thus, there arise the vital needs for the detailed assessments of the measures so provided, its quality of implementation so far and the level of satisfaction of the same among the different class of employees. The present study acts as a working paper with an objective to gather the opinion of the organized workforce in the Central Public Sector Enterprises with regards to their acceptance and satisfaction level of the various ‘Employees welfare and Social Security’ measures by the employers. However, the present study is restricted to two enterprises only and is undertaken with the following objectives: To analyze the opinions of the employees in respect of the labour welfare measures & social security benefits. To analyze the level of satisfaction or otherwise of the workers in respect of social security measures.